Revolution Imagined: Cause Advocacy, Consumer Rights, and the Evolving Role of NGOs in Thailand. (1st January 2014) - Munger, Frank
Abstract: This article describes the founding and evolution of a "Thai-style" NGO dedicated to consumer protection. Through a description of the NGO and the career of its founder, the article brings to light features of the evolution of NGO-based advocacy in Thailand from the student uprising in 1973 to the present. The legacy of the 1973 October Generation of activists continues to influence development of NGOs but new emphasis on rights has emerged since the era of constitutional reform in the 1990s. Many NGOs now make use of litigation to attempt to achieve social change, but litigation, like other long-standing methods of advocacy involving reliance on networks that penetrate government itself, reflect the particular opportunities and pathways for change opened by Thailand's politics.